Combining PD-1 or PD-L1 inhibitors with chemotherapy is a good strategy for the treatment of extensive small cell lung cancer: A retrospective analysis of clinical studies - Luo, Hao; Song, Guangbin; Wang, Dong; Li, Mengxia; Dai, Nan (Frontiers in Immunology, 2022)
Objectives To provide an updated systematic review and meta-analysis of published randomized controlled trials (RCTs) of the efficacy and safety of programmed cell death1 (PD-1)/programmed cell death ligand 1 (PD-L1) inhibitors combined with chemotherapy versus chemotherapy alone in the treatment of extensive-stage small-cell lung cancer (ES-SCLC). Methods Pubmed, Web of Science, Embase, Clinicaltrials and the Cochrane Library were systematically searched to extract RCTs of the efficacy and safety of PD-1/PD-L1 inhibitors combined with chemotherapy versus chemotherapy alone in the treatment of ES-SCLC from database inception to August 31, 2022. The literature was independently selected, information was extracted and the risk of bias of RCTs was evaluated according to inclusion and exclusion criteria. Stata14. 0 was used for meta-analysis. Results Six studies involving 2600 patients were included. The results of the meta-analysis showed that the combination of PD-1/PD-L1 inhibitors significantly improved OS(HR:0.73,95%CI:0.66-0.80; P<0.0001), prolonged PFS(HR: 0.66,95%CI:0.55-0.79; P<0.0001), and did not increase overall incidence of treatment-related adverse events(TRAEs) (RR: 1.03,95%CI:0.97-1.09; P=0.330) in ES-SCLC patients compared with chemotherapy alone. Subgroup analysis found that patients with negative PD-L1 expression (< 1%) benefited in OS, while patients with positive PD-L1 expression (≥1%) had no statistically significant difference in OS. There was a statistically significant difference in PFS between PD-L1 negative (< 1%) and PD-L1 positive (≥1%) patients. The addition of PD-1 inhibitor and PD-L1 inhibitor in chemotherapy regimen can improve OS and prolong PFS in patients with ES-SCLC. Conclusions PD-1/PD-L1 inhibitor combination chemotherapy significantly improves PFS and OS in ES-SCLC patients without increasing the overall incidence of TRAEs.